Therapeutic Effects of Laetiporus Sulphureus Culture Broth on Diabetic Foot Ulcer in Rats - Liu Y; Zhang Z; Su Z; Deng Y; Lin C; Tian W (Diabetes, Metabolic Syndrome and Obesity)
Yujiao Liu,1 Zixuan Zhang,1 Zhenhan Su,1 Yuhong Deng,2 Chuhui Lin,2 Wei Tian1 1School of Life Science and Biopharmaceuticals, Shenyang Pharmaceutical University, Shenyang, Liaoning, People’s Republic of China; 2Department of Clinical Nutrition, The Second Affiliated Hospital of Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Wei Tian, School of Life Science and Biopharmaceuticals, Shenyang Pharmaceutical University, 103 Wenhua Road, Shenhe District, Shenyang, 110016, Liaoning, People’s Republic of China, Email tianweiww@sina.comPurpose: To investigate the therapeutic effect of the culture broth of Laetiporus sulphureus on diabetic foot ulcer rats.Patients and Methods: The diabetic foot ulcer model was established by combined treatment of streptozotocin (STZ) and hindfoot injury in rats. The rats were divided into groups: control, model, low-dose, and high-dose of Laetiporus sulphureus culture broth. Blood sugar and wound area were measured. ELISA determined levels of TNF-α, IL-6, and VEGF. H&E staining observed damaged skin tissues.Results: Compared to the model group, the culture broth of Laetiporus sulphureus could lower blood glucose levels and decrease the wound area. It could notably decrease the concentration of TNF-α and IL-6, inhibit the expression of inflammatory factors in skin tissues, enhances the expression of VEGF and accelerate wound healing.Conclusion: The Laetiporus sulphureus culture broth can effectively facilitate wound healing of foot injury in diabetic rats and has a certain therapeutic effect on diabetic foot. The study explores an alternative therapy from natural sources to address a gap in diabetic foot ulcer management. It provides a foundation for further research on Laetiporus sulphureus as a novel treatment.Keywords: diabetic foot ulcer, Laetiporus sulphureus, TNF-α, IL-6, VEGF